Deep-ultraviolet sensing characteristics of transparent and flexible IGZO thin film transistors - Yoon, Jongwon; Bae, Ga-Young; Yoo, Seonggwang; Yoo, Jung Il; You, Nam-Ho; Hong, Woong-Ki; Ko, Heung Cho (ELSEVIER SCIENCE SA, 2020)
Recently, deep-ultraviolet (DUV) photodetectors with useful functions including transparency and flexibility have been developed for a real-time environmental monitoring, a wearable monitoring system, transparent wireless communication, and a smart window system. In this study, we investigate the DUV sensing characteristics of transparent and flexible IGZO thin-film transistors (TFTs) fabricated by a dry transfer printing, which is a very promising technique affording the device fabrication on unconventional surfaces. The fabricated TFT devices show high mechanical stability even at a bending radius of 1.4 mm, and the repeatable and gate bias-dependent DUV photoresponse characteristics. The gate bias-dependent photocurrent (I-ph) decay characteristics are likely attributed to the different surface re-adsorption rates of oxygen molecules depending on the gate bias polarity, which are qualitatively described based on energy band diagrams. In addition, the wavelength-dependent photoresponse characteristics of the IGZO TFT device upon UV illumination with lambda= 245 nm show a 10 times faster I-ph decay behavior than that upon UV illumination with lambda=365 nm. The result implies that the dissociative oxygen arising from the DUV illumination could accelerate the I-ph decay due to the increased surface adsorption. (C) 2019 Elsevier B.V. All rights reserved.